2017
DOI: 10.1007/s11010-017-3135-5
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene analysis in pathogenesis of surgically and non-surgically treated necrotizing enterocolitis in preterm infants

Abstract: Necrotizing enterocolitis (NEC) is one of the most severe and unpredictable complications of prematurity. There are two possible mechanisms involved in the pathogenesis of NEC: individual inflammatory response and impaired blood flow in mesenteric vessels with secondary ischemia of the intestine. The aim of this study was to evaluate the possible relationship between polymorphisms: Il-1β 3953C>T, Il-6 −174G>C and −596G>A, TNFα −308G>A, and 86 bp variable number tandem repeat polymorphism of interleukin-1 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
3
0
4
Order By: Relevance
“…• эндотелиальная NO-синтаза -путем выработки оксида азота, регулирует кровоток и целостность в слизистой оболочке кишечника [17], • гепарин-связывающий эпидермальный факторусиливает кишечный кровоток, снижает апоптоз клеток, стимулирует миграцию и пролиферацию энтероцитов [17].…”
Section: кишечный барьер как сложная функциональная система: физиолог...unclassified
See 1 more Smart Citation
“…• эндотелиальная NO-синтаза -путем выработки оксида азота, регулирует кровоток и целостность в слизистой оболочке кишечника [17], • гепарин-связывающий эпидермальный факторусиливает кишечный кровоток, снижает апоптоз клеток, стимулирует миграцию и пролиферацию энтероцитов [17].…”
Section: кишечный барьер как сложная функциональная система: физиолог...unclassified
“…Некротизирующий энтероколит (НЭК) является смертельным заболеванием, при котором современные диагностические инструменты недостаточны для доклинического выявления и предотвращения НЭК, а ранние прогностические биомаркеры могут быть полезны для выявления детей с высоким риском развития НЭК -этот тезис констатируют исследователи во всем мире [17,18]. Однако существуют сложности поиска диагностических маркеров, которые часто заключаются в ограниченной численности выборки, в частности, Hoff sten A, и соавторы обследовали 11 новорожденных с НЭК и исследовали у них 189 воспалительных, онкологических и сосудистых протеомных биомаркеров.…”
Section: некротизирующий энтероколит: перспективные биомаркеры повреж...unclassified
“…Such a finding highlights the possible role of VDR genetic variation on the overall interaction between vitamin D and the TLR4 cascade. An increasing number of reports have placed emphasis on the genetic predisposition of preterm infants to NEC [56][57][58][59][60][61] . However, due to lack of extensive research and coherence of results, validating studies remain necessary to elucidate the relationship between gene variation and NEC 62 .…”
Section: Respiratory Distress Syndrome Rds Is a Common Complication mentioning
confidence: 99%
“…As excessive inflammation is a hallmark of NEC, many investigators have examined the relationship of several pro-inflammatory cytokine gene polymorphisms and NEC, with varying results. Treszl et al 17, 18 , Heninger et al 19 , Henderson et al 20 , and Szpecht et al 22 have examined functional variants of several pro-inflammatory cytokines (including tumor necrosis factor-alpha, interleukin (IL)-1β, IL-4 receptor α-chain, IL-6, IL-18, and IL-10) and found no evidence of association of these genes with NEC. In contrast, Franklin et al 21 reported a positive association between IL-6 (rs1800795) variant and NEC in Caucasian neonates; while Tian et al 48 found a positive association between IL17F (rs763780) variant and NEC in a Chinese cohort.…”
Section: Candidate Gene Approachmentioning
confidence: 99%
“…In another study, Szpecht et al 22 more directly evaluated nitric oxide pathways by measuring polymorphisms of eNOS in 100 preterm infants, 22 of whom had NEC. They found that eNOS 894G>T polymorphism was more common in infants with NEC (OR 20, 95% CI 3.71–208.7, p=0.0004), and the eNOS 786T>C was increased in infants with surgical NEC (OR 4.88, 95% CI 1.33–21.99, p=0.013).…”
Section: Candidate Gene Approachmentioning
confidence: 99%